Influencer Credibility as A Source of Travel Information for Generation Z to Bali - Nariyani, Ni Nyoman; Agustini, Ni Putu Oka; Liestiandre, Hanugerah Kristiono (PT FORMOSA CENDEKIA GLOBAL, 2024)
The fast-paced advancement of technology requires tourism business managers to stay informed, particularly about platforms like Instagram, which is especially popular among Generation Z. Many users primarily turn to Instagram for entertainment and information, raising concerns about the reliability of the tourist information shared. This points to a need for better filtering of credible influencers to provide trustworthy tourism insights.This study explores how Generation Z evaluates the credibility of influencers as sources of information about tourism in Bali. Using a quantitative approach and the Multivariate Analysis of Variance Test (MANOVA), the research involved 110 respondents from various tourist categories, utilizing a purposive non-probability sampling method.The findings reveal that both domestic and foreign tourists assess influencers based on their attractiveness, which helps build trust in the content shared. Additionally, both male and female respondents have similar views on influencer credibility. This underscores the importance of establishing stricter criteria for influencer selection to ensure the accuracy of tourism-related information, benefiting both consumers and the tourism sector.